The use of video vignettes to measure health worker knowledge : Evidence from Burkina Faso - Banuri, Sheheryar; de Walque, Damien; Keefer, Philip; Haidara, Ousmane Diadie; Robyn, Paul Jacob; Ye, Maurice (Elsevier, 2022)
The quality of care is a crucial determinant of good health outcomes, but is difficult to measure. Survey vignettes are a standard approach to measuring medical knowledge among health care providers. Given that written vignettes or knowledge tests may be too removed from clinical practice, particularly where “learning by doing” may be an important form of training, we developed a new type of provider vignette. It uses videos presenting a patient visiting the clinic with maternal/early childhood symptoms. We tested these video vignettes with current and future (students) health professionals in Burkina Faso. Participants indicated that the cases used were interesting, understandable and common. Their performance was consistent with expectations. Participants with greater training (medical doctors vs. nurses and midwives) and experience (health professionals vs. students) performed better. The video vignettes can easily be embedded in computers, tablets and smart phones; they are a convenient tool to measure provider knowledge; and they are cost-effective instruction and testing tools.